Descripción histológica de la oogénesis y espermatogénesis del camarón de cultivo, Litopenaeus vannamei - Alfaro-Montoya, Jorge (2013)
This research describes detailed stages of oogenesis and spermatogenesis at histological level in the white shrimp of the western Pacific, Litopenaeus vannamei. Both processes were studied in cultured organisms under reproduction conditions in the laboratory. Oogenesis was histologically analyzed from the proliferation of 9 μm oogonia and their growth into primary oocytes passing through different phases of previtellogenesis: stages of synapsis, chromatin nucleolus, early perinucleolus and late perinucleolus of 84-94 μm. Primary vitellogenesis was observed in primary oocytes of 71-112 μm, containing acidophilic globules and surrounded by a layer of thick follicle cells (12-35 μm). Secondary vitellogenesis is evident in oocytes of 165-202 μm with numerous acidophilic granules in the cytoplasm and surrounded by thin follicle cells; then cortical crypts appear, indicating the stage of prematuration and preparation for ovulation. Spermatogenesis was characterized at light microscopy from spermatogonia and their gradual maturation into primary and secondary spermatocytes, early, mid and advanced spermatids and sperm. The process is synchronous in regions of seminiferous tubules, and asynchronous in neighboring tubules, generating cells at different stages up to mid spermatids in the testicles. Advanced spermatids and spermatozoa were only observed in the vasa deferentia; this finding appears not to be universal in Penaeidae.